Surgical Management of Cholelithiasis Cross-sectional study of 41 patients (Texas Journal of Medical Science, 2024)
Gallstones may be biochemically categorized into three types: cholesterol stones, brown pigment stones, and black pigment stones. There are two potential anatomical locations for gall stones: choledocholithiasis (in the common bile duct) and cholelithiasis (in the gall bladder). Gallstones can be symptomatic (showing symptoms) or asymptomatic (not showing symptoms). Low bile salt levels, impaired gall bladder motility, a high-cholesterol diet, and other similar factors are the main causes of gallstones. Factors that increase the likelihood of gall stones developing include being overweight, being female, having a history of the condition in the family, losing weight quickly, and not getting enough vitamin B12 or folic acid. Acute cholecystitis and feverish sickness characterized by right upper quadrant discomfort and tenderness (Murphy sign) are among the clinical manifestations